PENGARUH PERUBAHAN RETURN ON ASSETS, PERUBAHAN DEBT TO EQUITY RATIO DAN PERUBAHAN CASH RATIO TERHADAP PERUBAHAN DIVIDEND PAYOUT RATIO - Soesetio, Yuli (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2008)
Dividend Payout Ratio used to calculate all of revenue that will be accepted by stockholders as cash dividend, usually explained as percentage. This research was conducted to know several factors that affected change of Dividend Payout Ratio and to know the significance level and the correlation between dependent and independent variable. Analysis instrument used was parametric statistic. Based on the result of statistic test, Â The Change of Return on Asset (X1), The Change of Debt to Equity Ratio (X2),Â were able to explain dependent variable of the change Dividend Payout Ratio, and The Change of CashRatio canâ€™t explain dependent variable of the change Dividend Payout Ratio